No man is an island: community and commemoration on Norway's Utøya - Frydnes, Jørgen Watne (University of Massachusetts Press, 2025)
"On July 22, 2011, a white supremacist killed eight people at Oslo's Government Center in Norway and then terrorized the idyllic island of Utøya, where he executed sixty-nine more people, mostly teenagers. The country had never suffered such a massacre, and in the aftermath, the entire population was reeling. Utøya, the Norwegian Labor Party's summer camp for youth, a beloved place where many Norwegians learned about democratic values and processes, made lifelong friendships, and developed a vision for a just society, became mired in grief and discord. When Jørgen Watne Frydnes took on the daunting task of rebuilding the island and charting its future, he had to figure out a compassionate and just way forward. He made a radical decision: he set out to talk with each family of a murdered person, seeking to understand their needs and their hopes so that the future of the island could include their wishes and concerns. This emotionally grueling work, which was never considered in the scholarly literature on commemoration, led to a true renewal of Utøya, resulting in a meaningful memorial to those who were lost as well as beautiful surroundings for campers who come there to study democracy and peace. Frydnes's narrative, originally published in Norwegian, is structured around the seasons of the year and the landscape of the island, and tracks one person's account of learning how to remember, commemorate, and honor the dead, and acknowledge a mass tragedy, and yet also create a nurturing, aspirational space for hope. "--